Using Pneumatic Systems in the Representation of Historical Buildings Damaged in Earthquakes: The Case of Hatay - Esra İmamoğlu Yılmaz; Güray Yusuf Baş; Tayfur Emre Yavru; Semih Yılmaz (Doğal Afetler ve Çevre Dergisi)
As a result of the earthquakes centered in Kahramanmaraş in 2023, many historical buildings were destroyed. Since these structures represent the cultural memory of the city and its inhabitants, the renewal, reinforcement and restoration of these structures are essential. However, reconstruction or restoration of historical buildings are more costly, complex and time-consuming than constructing new ones. In reinforcement, renovation and restoration processes, various practices are implemented to preserve the cultural memories of the local inhabitants. As an innovative proposal within these practices a model that employs pneumatic system technology to represent earthquake-damaged historical structures has been developed and examined for its practical application possibilities. The results of the study indicate that the pneumatic system can be rapidly applied to different types and forms of buildings, that there are no size or height restrictions on system components, that transportation and labor are efficient, and that the recyclability of system materials will contribute to reducing the carbon footprint.